2014
DOI: 10.1016/j.ejc.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Fractional and integer matchings in uniform hypergraphs

Abstract: Abstract. A conjecture of Erdős from 1965 suggests the minimum number of edges in a kuniform hypergraph on n vertices which forces a matching of size t, where t ≤ n/k. Our main result verifies this conjecture asymptotically, for all t < 0.48n/k. This gives an approximate answer to a question of Huang, Loh and Sudakov, who proved the conjecture for t ≤ n/3k2 . As a consequence of our result, we extend bounds of Bollobás, Daykin and Erdős by asymptotically determining the minimum vertex degree which forces a mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For a 3‐graph H $H$, Hàn, Person, and Schacht [9] showed that δ1(H)>(59+o(1)))(|V(H)|2 ${\delta }_{1}(H)\gt (5\unicode{x02215}9+o(1))\left(\genfrac{}{}{0ex}{}{|V(H)|}{2}\right)$ is sufficient for the appearance of a perfect matching of H $H$. Kühn, Osthus, and Townsend [16] proved a stronger result: There exists a positive integer n0 ${n}_{0}$ such that if H $H$ is a 3‐graph with |V(H)|=nn0 $|V(H)|=n\ge {n}_{0}$, m $m$ is an integer with 1mn3 $1\le m\le n\unicode{x02215}3$, and δ1(H)>)(n12)(nm2 ${\delta }_{1}(H)\gt \left(\genfrac{}{}{0ex}{}{n-1}{2}\right)-\left(\genfrac{}{}{0ex}{}{n-m}{2}\right)$, then ν(H)m $\nu (H)\ge m$. For k{3,4} $k\in \{3,4\}$, Khan [12, 13] showed that there exists a positive integer n0 ${n}_{0}$ such that if H $H$ is a k…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a 3‐graph H $H$, Hàn, Person, and Schacht [9] showed that δ1(H)>(59+o(1)))(|V(H)|2 ${\delta }_{1}(H)\gt (5\unicode{x02215}9+o(1))\left(\genfrac{}{}{0ex}{}{|V(H)|}{2}\right)$ is sufficient for the appearance of a perfect matching of H $H$. Kühn, Osthus, and Townsend [16] proved a stronger result: There exists a positive integer n0 ${n}_{0}$ such that if H $H$ is a 3‐graph with |V(H)|=nn0 $|V(H)|=n\ge {n}_{0}$, m $m$ is an integer with 1mn3 $1\le m\le n\unicode{x02215}3$, and δ1(H)>)(n12)(nm2 ${\delta }_{1}(H)\gt \left(\genfrac{}{}{0ex}{}{n-1}{2}\right)-\left(\genfrac{}{}{0ex}{}{n-m}{2}\right)$, then ν(H)m $\nu (H)\ge m$. For k{3,4} $k\in \{3,4\}$, Khan [12, 13] showed that there exists a positive integer n0 ${n}_{0}$ such that if H $H$ is a k…”
Section: Introductionmentioning
confidence: 99%
“…is sufficient for the appearance of a perfect matching of H . Kühn, Osthus, and Townsend [16] proved a stronger result: There exists a positive integer n 0 such that if H is a 3-graph with…”
mentioning
confidence: 99%